Development of Holistic integrative pharmacy Based on Clinical Pharmacy - Xin ZHAO; Xiong LI (Journal of Holistic Integrative Pharmacy)
[Abstract]: With advances in modern medicine, life science technologies, economics, information technologies, and the Internet, the focus of clinical pharmacy is transitioning from drug product-oriented to patient-oriented. Current clinical pharmaceutical education curriculums cannot fulfill the requirements of preparing excellent clinical pharmacists and pharmaceutical management professionals. The professional training programs have failed to stay focused on the objective of providing scientific suggestions for clinical drug uses. Therefore, it is imperative to restructure clinical pharmaceutical education programs. This article discusses the definition, background, development, and integration approaches of holistic integrative pharmacy (HIP). The use of the schemes and methods of HIP building is proposed to prepare quality clinical pharmacy professionals who can adapt to the trends of a new era.